VALIDASI PERFORMA SATELIT PRESIPITASI GSMaP DALAM MENGESTIMASI CURAH HUJAN DI JABODETABEK - Rahman, Rahmat Nur; Indra , Indra (Pusdiklat BMKG, 2020)
Early in 2020 the Jabodetabek area was again shocked by the heavy rains which had an impact on flooding inalmost all of its areas, resulting in losses for the surrounding population. This condition encourages research on extreme rain events in the region. However, the limited distribution of rainfall observation points makes it necessary to use alternative types of satellite-based data. This study applies satellite rainfall estimation data from GSMaP (Global Satellite Mapping of Precipitation) which has been operated by BMKG as one of the rainfall data for analysis of rainfall events. The GSMaP spatial resolution of 0.25o and the availability of data since 2000 make this data usable as alternative rainfall data. This study aims to determine the performance of GSMaP on observational data for the Jabodetabek area which includes AWS Manggarai, ARG Jagorawi, AWS UI, South Tangerang Staklim, and ARG Jatiasih in estimating rainfall. For this reason, a performance validation test was carried out on December 31, 2019 - January 11, 2020 using a scatter plot to determine the correlation between GSMaP performance in estimating rainfall. The results showed a correlation value of 0.72 which means it has a strong correlation level, so that GSMaP has a good performance for estimating rainfall in the Jabodetabek area.